EVALUASI IMPLEMENTASI PROGRAM JAMKESDA KABUPATEN JEPARA - Nanda Galih Febriyan; Ahmad Taufiq; Sulistyowati . (Journal of Politic and Government Studies, 2016)
Nowadays,the level of citizens health in Indonesia is not good enough, that’shappened because difficulties of the access to get the health services. Thedifficulties of access are influenced by many factors, one of them is not having afinancials capability to pay the health services which are expensive. To cope thatproblem, the central government makes a program to allow the poor citizens toget health services free of charge through Nationals Health Assurance program(JKN). Although the Nationals Health Assurance program (JKN) has run well, inpractical it still has many weaknesses. The main weakness of the data of theprogram’s receiver isn’t precise and up to date, and it makes many region’scitizens who are proved that they don’t have the financial capability but they stillare not on the program receiver’s list. This research talks about the evaluation ofJepara Goverment’s program to cope the weakness of Nationals Health Service(JKN) implemented. Jepara region’s government has been implemented the PoorCitizens Health Service’s program or known as Regional Health Assuranceprogram (Jamkesda) which has a purpose to take care Jepara’s poor citizenswhose has not registered on National Helath Assurance Program (JKN).Therefore, Jepara’s poor citizens still get the health services for free. Thisevaluation used describtive qualitative method with George Edward III as a maintheory which focused on vital variables which have most influences for program’ssuccess, there are Communication, Resources, Dispotition, and BureaucracyStructure, also supported with Triangulation theory to make better data.Obstacles and settlements of the Regional Health Assurance program (Jamkesda)has also been explained. Result of this research shows that the implementation ofRegional Health Assurance (Jamkesda) is running quite well to give the freehealth service for Jepara’s poor citizens, so the purpose to make poor citizens feelsafe through health assurance’s program can be accomplished. The main obstacleof this program is the promotion hasn’t spreaded well through all citizens andbecause of that miss targeting of program’s participants oftenly happened, theweakness of monitoring also makes people who shouln’t get this free chargeservice can use this program. The advices from researcher for the main actor ofthis program Jepara Health Department (DKK) is DKK has to be more explicit inregulations to arrange people who deserve and who don’t get this healthassurance, and coordinate from the bottom to the top in order to that missedtargets never occurred again.